Holographic boundary conformal field theory with T T ¯ $$ T\overline{T} $$ deformation - Zhi Wang; Feiyu Deng (Journal of High Energy Physics)
Abstract We propose a holographic dual of boundary conformal field theory (BCFT) with T T ¯ $$ T\overline{T} $$ deformation, i.e. of T T ¯ $$ T\overline{T} $$ BCFT. Our holographic proposal distinguishes two types of T T ¯ $$ T\overline{T} $$ BCFTs, depending on whether the T T ¯ $$ T\overline{T} $$ deformation deforms the boundary. For the boundary-deformed case, we find that boundary entropy serves as an effective measure to quantify the impact of boundary deformation. In this scenario, we calculate the energy spectrum for the T T ¯ $$ T\overline{T} $$ BCFT within a finite interval to support the proposed dual. For the boundary-undeformed case, we calculate the entanglement entropy and Rényi entropy from both the field theory side and the gravity side, and find that they match.